PEMBERIAN HAK HADHANAH YANG DIBERIKAN OLEH AYAH BAGI ANAK YANG BELUM MUMAYIZ AKIBAT TERJADINYA PERCERAIAN MENURUT PERSPEKTIF HUKUM ISLAM: Wafda Lyinna - admin, admin (Reformasi Hukum, 2017)
The purpose of this study is to: (a) obtain a description of the right of the father to the unmarried children due to the divorce according to the perspective of Islamic law, (b) To obtain an explanation of the position of the child according to Law Number 1 of 1974 and Islamic law, and (c) To obtain an explanation of the legal consequences of a father who fails to perform his obligations in the care of a child who has not been mumayiz due to divorce under Islamic law. This research used normative juridical methods. Research Results: There are no verses of the Qur'an and the hadith that expressly stipulates the gift of hadhanah given by the father to the unmarried child, as described in Article 105 letter (a) stating that the maintenance of a child who has not been mumayiz or 12 years of age is her mother's right. However, in solving divorce cases the writers adopt the basis of law Article 41 letter a Act Number 1 Year 1974 About Marriage. The judge uses the method of problem-solving maslahah al-mursalah. The position of a child in Islam is very high and noble. The Qur'an and Hadith do not explain and explain in detail about the legal consequences of a father who does not perform his obligations in the care of a child who has not been mumayiz due to the divorce. Conclusion: (a) When there is a dispute in the household should be settled by way of peace and deliberation first, and (b) Judge in deciding a matter, to be more professional and clinging to the Qur'an, the Prophet's Sunnah.